Catfish Jambal Roti Pangasius sp: Product Characteristics based on Salt Concentration and Fermentation Length - Amir, Nursinah; Syahrul, Syahrul; Metusalach, Metusalach; Hafifah, Nur (Torani Journal of Fisheries and Marine Science, 2024)
Catfish (Pangasius sp.) has high nutritional value and can be used to make various products, one of which is jambal roti. This research aims to determine the characteristics of jambal bread based on fermentation time and salt concentration. The research used an experimental method with a completely randomized design (CRD) factorial pattern with three levels of fermentation duration (A), namely A1:24 hours, A2:36 hours and A3:48 hours at two levels of salt concentration (B), namely B1:25% and B2:30% repeated 3 times. The parameters assessed are sensory characteristics, total plate number, water content, ash content and salt content. The results showed that the sensory values ​​were appearance (7.82-8.30), smell (8.14-8.25), taste (8.04-8.41), texture (7.66-8.68), mold (9.00). The research results also showed total plate number (0-1.037 x 103), water content (26.99 - 32.29%), ash content (18.98 - 23.34%) and salt content (19.44 - 24,50%). ALT meets standard quality requirements (SNI 2721.1-2009), water content complies with SNI (8376:2017), ash content does not meet the SNI (8376:2017), and salt content in 2 samples (A1B2 and A2B2) only meets SNI (8376:2017). The characteristics of Catfish Jambal Roti Patin this study, in general, are in accordance with SNI (8376:2017)